Examining the link between reward and response inhibition in individuals with substance abuse tendencies. (1st January 2019) - Byrne, Kaileigh A.; Worthy, Darrell A.
Highlights: The role of drug use on rewarded and unrewarded response inhibition was tested. The effect of spontaneous eyeblink rate (EBR) was also examined. Results indicated an interaction between drug use and EBR on response inhibition. Drug users with low EBR showed deficits in incentivized response inhibition. Reward motivation hinders inhibitory control in drug users with low EBR. Abstract: Background: Substance use problems are often characterized by dysregulation in reward sensitivity and inhibitory control. In line with this representation, the goal of this investigation was to determine how substance abuse tendencies among university students affect incentivized response inhibition. Additionally, this study examined whether striatal dopamine moderates the impact of substance use on response inhibition performance. Methods: The sample included ninety-eight university students. Participants completed this prospective experimental study at an on-campus laboratory. All participants completed substance abuse and disinhibition subscales of the Externalizing Spectrum Inventory-Brief Form. Using a within-subjects design, participants then performed the Stop Signal Task under both neutral (unrewarded) and reward conditions, in which correct response cancellations resulted in a monetary reward. Striatal tonic dopamine levels were operationalized using spontaneous eyeblink rate. Results: The outcome measures were Stop Signal Reaction Time (SSRT) performance in the unrewarded and rewarded phases of the task. A hierarchical linear regression analysis, controlling for trait disinhibition, age, gender, and cigarette smoking status, identified an interactive effect of substance use and striatal dopamine levels on incentivized SSRT. Substance abuse tendencies were associated with slower SSRT and thus poorer inhibitory control under reward conditions among individuals with low levels of striatal dopamine ( F  = 7.613, p = .007). Conclusions: This work has implications for research examining advanced drug use trajectories. In situations in which rewards are at stake, drug users with low tonic dopamine may be more motivated to seek those rewards at the expense of regulating inhibitory control.